‘REMOTIO AB ORDINEM’ WYDALENIE DEKURIONA (RADNEGO) Z ‘ORDO DECURIONUM’ (RADY MIASTA) - Bronisław Sitek (Zeszyty Prawnicze)
‘REMOTIO AB ORDINEM’. COUNCILLORS’ (‘DECURIO’) EXPULSION FROM THE CITY COUNCIL (‘ORDO DECURIONUM’) Summary In the light of the Polish law every citizen who has all civil rights can perform a function of a councillor. Polish legislation, with the exception of the requirement of age, does not introduce any further formal requirements for candidates for that office. A councillor needs not to have any professional or moral qualifications. Although there are codes of councillors’ conduct which relate to such values as honesty and integrity, however they do not introduce any sanctions for their violation. Source analysis shows that in the Roman law the major causes of expulsion from the city council include: conducting an immoral life, performing an infamous profession (actual infamy), conviction on the basis of a disgracing civil action (iudicia privata) or a disgracing public action (iudicia publica) and criminal expulsion from the army (missio ignominiosa). To the professions causing infamy were also included such professions as gladiator, actor, herald, gravedigger, or guardian in a theatre. Civil actions disgracing lost party were: fiduciae actio pro socio, actio tutelae, actio mandati. To the disgracing civil actions, but with the tort nature, were also included actio porter, actio iniuriarum and actio lot. Sentencing in the public was always associated with an additional penalty that generated discredit on the honour, or to infamy. The same was in the case of criminal deportation from the army.